Experimental investigation of the effect of the addition of Aerosil 200 nanoparticles on the water absorption of polymer concrete - Fattahi, A. M.; Safaei, Babak; Moaddab, Elham; Pezeshki, Zahra (Techno-Press, 2023)
In this work, the effect of the addition of Aerosil 200, an insulating resin applied in many industries, on the water absorption of cement plast mixture has been experimentally evaluated. First, the preparation stages of cement plast mixture was evaluated based on corresponding standards and then, the effect of the addition of Aerosil 200 nanoparticles (NPs) to cement plast mixtures with sand weight percentage range of 0-0.1% on the variation of water absorption properties was evaluated based on National Standard Institution of Iran 20185 for Concrete Flooring Blocks - Requirements and Test Procedures. Based on the obtained results, it could be found that excessive addition of NPs did not affect the physical properties of the final product. Water absorption percentage was increased in the weight percentage of cement. By the increase of the amount of Aerosil 200 NPs in the prepared cement plast mixture, the percentage of water absorption in weight percentage of sand was decreased. Cement plast with NPs presented significantly lower water absorption than that without NPs.
Keywords: aerosil nanoparticles; cement plast; water absorption property; weight ratio